Interpretasi Pragmatik melalui Implikatur Konvensional dan Nonkonvensional dalam Debat Capres Indonesia 2024 - Ika Arifianti; Dewi Kusumaningsih (Badan Pengembangan dan Pembinaan Bahasa, 2024)
Presidential candidate debates play an important role in the campaign by becoming an arena for brainstorming and complex communication strategies. This research uses a pragmatic perspective to understand the dynamics of language in presidential debates, uncover the implicit meaning behind the candidates' speeches, and identify rhetorical strategies that influence the audience. With a theoretical approach that tests Grice's critical pragmatic analysis and conversational implication theory as well as descriptive-qualitative methods, this study analyzes the speeches of presidential candidates in the 2024 Indonesia presidential debate. Data was collected using the Free Listening and Conversation (SBLC) technique, which was recorded for further analysis in written form. The results of the analysis showed that there were conventional and non-conventional implications that candidates used to convey messages directly and subtly. This research also highlights the importance of language politeness according to Grice in political communication. The occurrence of implicature as a powerful tool in political debates emphasizes the importance of contextual understanding, and provides a new contribution to the study of political communication with a focus on presidential debates as a highly competitive and dynamic context. This research enriches the understanding of rhetorical strategies in political communication and the importance of pragmatic analysis in political debates. AbstrakDebat calon presiden (capres) memainkan peran penting dalam kampanye dengan menjadi arena adu gagasan dan strategi komunikasi kompleks. Penelitian ini menggunakan perspektif pragmatik untuk memahami dinamika bahasa dalam debat capres, mengungkap makna implisit di balik ujaran kandidat, serta mengidentifikasi strategi retorika yang mempengaruhi audiens. Dengan pendekatan teoretis yang menguji analisis pragmatik kritis dan teori metodologis percakapan menerapkan metode deskriptif-kualitatif, penelitian ini menganalisis tuturan calon capres dalam debat capres Indonesia 2024. Data dikumpulkan melalui teknik Simak Bebas Libat Cakap (SBLC), yang melalui rekaman untuk dianalisis lebih lanjut dalam bentuk tulisan. Hasil analisis menunjukkan adanya implikatur konvensional dan non-konvensional yang digunakan kandidat untuk menyampaikan pesan secara langsung maupun halus. Penelitian ini juga menyoroti pentingnya maksim kesantunan berbahasa menurut Grice dalam komunikasi politik. Terjadinya implikatur sebagai alat yang kuat dalam debat politik, menekankan pentingnya pemahaman kontekstual, serta memberikan kontribusi baru dalam studi komunikasi politik dengan fokus pada debat capres sebagai konteks yang sangat kompetitif dan dinamis. Penelitian ini memperkaya pemahaman tentang strategi retorika dalam komunikasi politik dan pentingnya analisis pragmatik dalam debat politik.